Participación legislativa en la construcción de derechos de propiedad intelectual - Mora Solano, Sindy (2022)
This article analyses the legislative participation in the construction of intellectual property rights, specifically those referring to the property of improved plant varieties, which are a requisite for the Central America Free Trade Agreement (CAFTA). Research findings show that social differentiation is expressed as inequity in the search of spaces for legislative discussion.